Remarks on the Cortical Structure of Late Paleozoic "Phylloid Algae". (September 2014) - Corrochano, Diego; Vachard, Daniel
Abstract : The cortical structure of the green anchicodiacean alga Anchicodium in the Pennsylvanian Dueñas Formation of the Cantabrian Zone (northwestern Spain) is described and illustrated. Anchicodium is characterized by a broad phylloid or leaflike calcified thallus, consisting of a bilateral cortex and a poorly calcified central medulla. The organization and morphology of the cortical system have been revealed with great detail using cathodoluminescence microscopy. Anchicodium cortex is composed of up to three (four?) orders of dichotomized branched cortical siphons that are usually swollen at the center; primary siphons are bulbous and are followed by elongate cylindrical siphons. Cortical siphons are preserved as dull-bright luminescent molds filled with micrite or microsparite, and contrast sharply with the surrounding non-luminescent calcite infilling the intersiphonal spaces, originally occupied by aragonite. Anchicodium in the Dueñas Formation exhibits a variety of preservational stages. Through a compilation of the taxonomic nomenclature and morphologic re-interpretations, it is concluded that some late Paleozoic anchicodiacean algae might represent diagenetic stages of Anchicodium or Eugonophyllum without any taxonomic significance. This conclusion is suggested particularly for the taphotaxon Ivanovia .